Pengaruh Firm Size dan Sales Growth terhadap Struktur Modal pada Sektor Food and Beverage yang terdaftar di Bursa Efek Indonesia tahun 2020-2024 - Mesya Dwiyana; Irfan Achmad Musadat; Agung Pramayuda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the effect of Firm Size (X1) and Sales Growth (X2) on Capital Structure (Y) in the Food and Beverage sector listed on the Indonesia Stock Exchange in 2020-2024. Capital Structure in this study is proxied by the Debt to Equity Ratio (DER), Firm Size is measured based on the natural logarithm of total assets, and Sales Growth is measured based on the annual Sales Growth rate. This research employs a quantitative method with a descriptive and verificative approach. The sample consists of 18 companies selected through purposive sampling based on specific criteria. The data used are secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange and the respective companies. The analytical techniques applied include the classical assumption test and multiple linear regression analysis. The results show that partially, Firm Size has no significant effect on Capital Structure with a value of 0.463, and Sales Growth has no significant effect on Capital Structure with a value of 1.317. Simultaneously, Firm Size and Sales Growth have no significant effect on Capital Structure with a value of 1.035.